Development of a numerical simulation method for modelling column breakthrough from extraction chromatography resins. Issue 12 (28th May 2021) - Burrell, Frances M.; Warwick, Phillip E.; Croudace, Ian W.; Walters, W. Stephen
Abstract : A numerical simulation method was developed in LabVIEW using rate constants derived from batch experiments. The successful application to chromatographic breakthrough demonstrates potential for integration with automated radioanalytical systems. Abstract : A numerical simulation method has been developed to describe the transfer of analytes between solid and aqueous phases and assessed for a commercially available extraction chromatography resin (UTEVA resin). The method employs an ordinary differential equation solver within the LabVIEW visual programming language. The method was initially developed to describe a closed batch system. The differential equations and kinetic rate constants determined under these conditions were then applied to the flow-through column geometry. This was achieved by modelling the resin bed as a series of discrete vertically stacked sections, thereby generating an array of solid and aqueous concentration values. Axial flow was simulated by the advancement of the aqueous phase values by one array position with the value advancing from the final array position representing the column output concentration. An investigation into the observed difference in breakthrough profiles obtained under repeated conditions revealed the relative tolerance of the numerical simulation method to errors in each input parameter. Additional physical processes such as backpressure and leaching of the extractant were considered as an explanation for observed inconsistencies between experimental and simulated datasets. An elution sequence featuring multiple eluents was also simulated, demonstrating that the prediction of analyte separation sequences is possible. The potential to develop the LabVIEW coding into user friendly software with an extendable kinetic database is also discussed. This software will be a useful tool to radiochemists particularly in the development of new analytical methods using automated separation systems.